Analysis of the F Antigen-Specific papA Alleles of Extraintestinal Pathogenic Escherichia coli Using a Novel Multiplex PCR-Based Assay - Johnson, James R. (American Society for Microbiology, 2000)
Polymorphisms in PapA, the major structural subunit and antigenic determinant of P fimbriae of extraintestinal pathogenic Escherichia coli, are of considerable epidemiological, phylogenetic, and immunotherapeutic importance. However, to date, no method other than DNA sequencing has been generally available for their detection. In the present study, we developed and rigorously validated a novel PCR-based assay for the 11 recognized variants of papA and then used the new assay to assess the prevalence, phylogenetic distribution, and bacteriological associations of the papA alleles among 75 E. coli isolates from patients with urosepsis. In comparison with conventional F serotyping, the assay was extremely sensitive and specific, evidence that papA sequences are highly conserved within each of the traditionally recognized F serotypes despite the diversity observed among F types. In certain strains, the assay detected serologically occult copies of papA, of which some were shown to represent false-negative serological results and others were shown to represent the presence of nonfunctional pap fragments. Among the urosepsis isolates, the assay revealed considerable segregation of papA alleles according to O:K:H serotype, consistent with vertical transmission within clones, but with exceptions which strongly suggested horizontal transfer of papA alleles between lineages. Sequencing of papA from two strains that were papA positive by probe and PCR but F negative in the new PCR assay led to the discovery of two novel papA variants, one of which was actually more prevalent among the urosepsis isolates than were several of the known papA alleles. These findings provide novel insights into the papA alleles of extraintestinal pathogenic E. coli and indicate that the F PCR assay represents a versatile new molecular tool for epidemiological and phylogenetic investigations which should make rapid, specific detection of papA alleles available to any laboratory with PCR capability.